The prevalence of peripheral intravenous cannulae and pattern of use: A point prevalence in a private hospital setting - Wong, K.; Cooper, A.; Brown, Janie; Boyd, L.; Levinson, M. (Wiley-Blackwell Publishing, 2018)
AIMS AND OBJECTIVES: To determine the prevalence and pattern of use of peripheral intravenous cannulae in hospital wards. BACKGROUND: Peripheral intravenous cannulae are commonly used in acute health care to directly access the bloodstream for the administration of medications, intravenous fluids and blood products. Peripheral intravenous cannulae are associated with multiple adverse events including hospital-acquired bloodstream infection, thrombophlebitis and pain/discomfort. Administration of intravenous fluids is associated with impaired mobility and nocturia which may increase falls risk in the older people. DESIGN: Observational, point prevalence study. METHODS: Three private hospitals comprising a total of 1,230 beds participated in the study. Nurses recorded the presence of a peripheral intravenous cannulae, duration of insertion, state of the dressing and whether the peripheral intravenous cannulae was accessed in the previous 24 hr and for what purpose. Nurses were also asked whether they would replace the peripheral intravenous cannulae should it fail. RESULTS: Approximately one-quarter of patients had a peripheral intravenous cannulae, the majority of which had been present for <24 hr. The major use of the peripheral intravenous cannulae was antibiotic administration. Administration of intravenous fluids occurred in the presence of normal oral fluid intake. Nurses would not replace one-third of peripheral intravenous cannulae in the event of failure. A majority of patients were at increased falls risk, and one-third of these were receiving intravenous fluids. CONCLUSIONS: There is room for improvement in the utilisation of peripheral intravenous cannulae, particularly in removal and associated use of intravenous fluids. Alternative strategies for medication administration and timely switch to the oral route may reduce the risks associated with intravenous fluids. RELEVANCE TO CLINICAL PRACTICE: Vigilance is required in the use of peripheral intravenous cannulae. Consider transition of medication administration to oral intake where possible to minimise risks associated with the use of invasive devices and increased fluid intake.